Digital Technologies Transforming Indian Agriculture : A Survey - Yadav, Priyanka G. (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 7 No 3 & 4 (2020): Journal of Advanced Research in Instrumentation and Control Engineering(ISSN: 2456-1398), 2021)
As a source of livelihood agriculture remains the largest sector of Indian economy. It provides employment to 58.2% of the population. The social transformation of the country and the economic growth depends on the performance of the agriculture sector. The huge and disparate climatic and crop diversity across India, it is a challenge to keep the farmers informed about the best practices in agricultural processes. The most developed economies have mechanised farming and reduced dependency on rains through state interventions and good planning, Indian farmers still plod along with obsolete farming techniques to support a growing population. Achieving sustainable agricultural systems will require transformative changes in markets, policy, and science. Internet initiatives for Rural and agriculture development must consider the fact that different regions; organizations and communities have different applications and technical needs. This paper focuses on understanding the concept of digital agriculture and how it propels the development of Indian agriculture. How to cite this article: Yadav PG, Yadav VR. Digital Technologies Transforming Indian Agriculture: A Survey. J Adv Res Instru Control Engg 2020; 7(3&4): 9-13